2020
DOI: 10.3892/or.2020.7619
|View full text |Cite
|
Sign up to set email alerts
|

Propofol suppresses the progression of non‑small cell lung cancer via downregulation of the miR‑21‑5p/MAPK10 axis

Abstract: Non-small cell lung cancer (NSCLC) accounts for >80% of lung cancer cases and is the leading cause of cancer-associated mortality worldwide. Propofol is an anesthetic drug frequently used during tumor resection. It is also known to exert inhibitory effects on cancer. Although the role of propofol in NSCLC has been reported, its underlying mechanisms remain unknown. The present study aimed therefore to investigate the mechanisms of propofol action on NSCLC. Starbase V3.0 project was used to analyze the expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…Propofol has presented significant anticancer functions in several models. It has been reported that propofol inhibits the development of nonsmall cell lung cancer by downregulating the miR215p/MAPK10 axis[ 24 ]. Propofol represses malignant progression of pancreatic cancer cells by reducing NMDA receptor[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has presented significant anticancer functions in several models. It has been reported that propofol inhibits the development of nonsmall cell lung cancer by downregulating the miR215p/MAPK10 axis[ 24 ]. Propofol represses malignant progression of pancreatic cancer cells by reducing NMDA receptor[ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some references have confirmed that propofol is implicated in lung cancer development. For instance, propofol has been reported to alleviate cell viability and facilitate cell apoptosis in NSCLC by inhibiting miR‐21‐5p and elevating MAPK10 21 . Liu et al discovered that propofol restrained lung cancer cell growth and metastasis via activating miR‐1284 22 .…”
Section: Discussionmentioning
confidence: 99%
“…MAPK10, a member of the MAPK family, plays a key role in cancer initiation and progression by acting as an integration point for multiple biochemical signals [21,22]. There is increasing evidence that it acts as a microRNA target to play a tumor-promoting or tumorsuppressing role [23][24][25]. Gao et al [26] revealed that miR-335-5p suppressed GC progression by targeting MAPK10.…”
Section: Discussionmentioning
confidence: 99%